Pathogenicity of Rhizoctonia solani AG 1-IA on major weeds prevalent in rice and maize ecosystem in Meghalaya - RAJESH KUMAR, THANGASWAMY RAJESH and GAJANAN T. BEHERE, ROW SAVEINAI, PANKAJ BAISWAR* (Indian Phytopathology, 2017)
Rhizoctonia solani Kühn (Teleomorph: Thanatephorus cucumeris) is an economically important soil borne basidiomycetous pathogen of worldwide distribution. It causes sheath blight disease of rice and banded leaf and sheath blight (BLSB) disease in maize. Twenty three lowland rice weeds and thirty one upland (maize) weeds were collected and used. Rice isolate (SRS) was pathogenic on all the lowland rice and upland weeds. Maize isolate (RSM2) was not pathogenic on Cyperus difformis, C. haspans, C. odoratus, Sagittaria sagittifolia, Celosia argentea, Commelina diffusa and Floscopa scandens. Minimum days for scleriotia formation was 3 days on C. bengalensis, maximum sclerotia production was observed on Echinochloa crusgalli (14 nos.) with the isolate SRS. Minimum days for sclerotia formation was 2 days after inoculation on Euphorbia hirta, Fimbristylis dichotoma, Rotala indica and Scirpus juncoides. Maximum sclerotia production was observed on Alternanthera philoxeroides (11 nos.) with the isolate RSM2. Area under disease progress curve was calculated and mean separation was done using REGWQ test (Ryan/Elinot/Gabriel/Welsch procedure). The weeds Ageratum houstonianum (10.2), A. sessilis (14), A. philoxeroides (25.3), Imperata cylindrica (14), Paspalum distichum (17.8) and Ambrosia artemisiifolia (23.3) were susceptible whereas Dactyloctenium aegyptium (115.6), E. colona (115.6) and Bidens pilosa (111.9) were highly susceptible to the isolate SRS. The weed A. houstonianum (43.7) was susceptible and R. indica (267.4) and E. hirta (266.2) were highly susceptible to the isolate RSM2.